Pengaruh Work-Life Balance dan Fleksibilitas Kerja Terhadap Employee Engagement pada ASN Dinas Energi dan Sumber Daya Mineral Provinsi Lampung - Wiranti Putri Retnosari; Iskandar Ali Alam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The dynamic development of work systems in the public sector requires civil servants to adapt to increasingly complex administrative and technical workloads. This condition highlights the importance of work-life balance and work flexibility in fostering employee engagement. This study aims to analyze the effect of work-life balance and work flexibility on employee engagement among civil servants at the Department of Energy and Mineral Resources of Lampung Province.This study employs a quantitative approach using a survey method involving 60 respondents selected through the Slovin formula. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression. The results indicate that work-life balance and work flexibility have a positive and significant effect on employee engagement, both partially and simultaneously. These findings suggest that improving work-life balance and work flexibility can enhance employee engagement within public sector organizations